Il problema dell’unicità e della trascendenza di Dio nella Bibbia ebraica - Della Pergola, Fabio (Il sogno della farfalla, 2014)
The numerous studies on the origins of monotheism, without omitting the role of the heretic pharaoh Akhenaton and Zoroastrianiam, generally agree in locating the affirmation of the idea of a unique, transcendent, absolute God, within the Jewish religion that succeeded the Babylonian exile. In the last forty years a totally innovative reading of the Hebrew texts was proposed by Carlo Enzo, a Bible scholar, whose criticism of well-known certainties provoked, among other things, a strong reaction from the Catholic Church. This article aims to explore Enzo’s interpretation, without failing to synthetically place the biblical writings into the context of the historical reality of the pre-Christian Middle East.